PERAN CASE MANAGER DAN FUNGSI MANAJERIAL KEPALA RUANG TERHADAP MUTU PELAYANANKEPERAWATAN DAN PATIENT-CENTERED CARE DI RUMAH SAKIT - Metilda; Rani Puspita; Ade Lulu; Astriani Hapsari; Grace A.C.Z; Intan Jesica (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
This literature review aims to provide a comprehensive overview of the contributions of case managers and ward managers in enhancing patient-centered care and improving the efficiency and quality of nursing services in hospitals. The review integrates findings from various national and international studies employing qualitative, quantitative, mixed-methods, and literature review designs. The synthesis shows that case managers play a crucial role in improving communication, care coordination, service continuity, patient satisfaction, and the control of quality and costs. Meanwhile, the managerial functions of ward managers—ranging from planning, organizing, directing, to supervising—are closely related to nurses’ performance, the completeness of documentation, the implementation of a patient safety culture, and adherence to clinical standards. However, the implementation of both roles continues to face challenges, such as limited training opportunities, insufficient supporting regulations, suboptimal interprofessional collaboration, and high workloads. Overall, this review highlights the importance of strengthening managerial competencies, improving supervision, formalizing case management systems, and enhancing organizational support to achieve high- quality and patient-centered nursing care.